Development Media Learning Geography with Applications Kahoot! as Media Evaluation Results Study Students in SHS 10 Padang - Iswara, Dedi; Suasti, Yurni; Ernawati, Ernawati (Postgraduate School, Universitas Negeri Padang, 2023)
Learning media is one of the supporting components of learning. Learning media has the benefit of increasing student interest and creativity, besides that learning media also influences student learning interest. The media used should follow current developments in science and technology. The media also helps in evaluating student learning outcomes. The purpose of this study is to describe the feasibility, effectiveness, and student responses regarding the use of Kahoot! in learning activities as a medium for evaluating learning outcomes. The development model used by researchers, namely the 4D model, is formed from 4 main stages such as: define, design, develop, and disperse. The results of validation by material experts obtained a proportion of 84%